1997
DOI: 10.1021/jp962905y
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemistry of Molecules in the B−N−Cl−H System:  Ab Initio Predictions Using the BAC-MP4 Method

Abstract: A self-consistent set of thermochemical data for 33 molecules in the B-N-Cl-H system are obtained from a combination of ab initio electronic structure calculations and empirical corrections. Calculations were performed for both stable and radical species. Good agreement is found between the calculations and experimental heats of formation for most molecules containing B, H, and Cl. In addition, the BAC-MP4 and experimental heats of formation for H 3 B:NH 3 are also in reasonable agreement, suggesting that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 56 publications
6
43
0
Order By: Relevance
“…Since it is not a pair of electrons but a single electron to be filled in one orbital of species of HBN (6), the B-N bond in it is thus weaker than that of BNH (5), which results in the B-N bond distance for HBN (6) being longer than that of BNH (5). The structure parameters are close to Allendorf and Melius's result [10,15].…”
Section: Stationary Pointssupporting
confidence: 85%
“…Since it is not a pair of electrons but a single electron to be filled in one orbital of species of HBN (6), the B-N bond in it is thus weaker than that of BNH (5), which results in the B-N bond distance for HBN (6) being longer than that of BNH (5). The structure parameters are close to Allendorf and Melius's result [10,15].…”
Section: Stationary Pointssupporting
confidence: 85%
“…Theoretical research found in the literature includes thermodynamic equilibrium calculations for mixtures involving B/F/N/H [1][2][3][4][5], B/Cl/N/H [4,5], and B/N/H [4], as well as limited kinetics studies of the reactions between BCl 3 and NH 3 [6,7]. P. R. P. Barreto developed a kinetic and surface mechanism to explain the growth of boron nitride [8 -11] (private communication, 2000); this mechanism is constantly upgrading, including new reaction and new species.…”
Section: Introduction Tmentioning
confidence: 99%
“…13 Dissociation of the first Al-CH 3 bond in trimethylaluminum is more than 20 kcal mol -1 weaker than the same bond in trimethylborane. Dissociation energies for bonds between boron and chlorine, 21 however, are very similar to those between aluminum and chlorine. Data for boron hydroxides are sparse, but heats of formation reported by Gurvich et al 2 indicate that the analogous aluminum bonds are weaker as well.…”
Section: Amentioning
confidence: 89%
“…In the Supporting Information (Tables S7 -S11), we also provide raw electronic energies at the G2 level, atomic coordinates, vibrational frequencies, moments of inertia, and polynomial fits of the thermodynamic data suitable for use with the CHEMKIN software. 17 As has been typical in previous publications involving the BAC-MP4 series, 15,16,[18][19][20][21][22][23][24][25] we focus our discussion on the predicted thermochemical parameters, rather than on the ab initio calucations themselves. .…”
Section: Amentioning
confidence: 99%